2019
DOI: 10.1002/bab.1751
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of curcumin‐loaded polymeric nanomicelles to interference with amyloidogenesis through glycation method

Abstract: Amyloid fibrils, including β-amyloid (Aβ) fibrils, are protein aggregates that form under certain conditions, associated with neurodegeneration that interfere with neural synaptic transmission resulting in some neural disorders, such as Alzheimer's disease. The aim of this study is to inhibit amyloidogenesis by using preparatory polymeric nanomicelles as therapeutic agents and also as nanocarriers for curcumin to target Aβ fibrils through the glycation method of bovine serum albumin (BSA) in the presence of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…First, it has exceptionally low water solubility (11 ng/mL in aqueous buffer pH 5.0), which means that it is eliminated from the body quickly and has a low oral bioavailability. It is soluble in dichloromethane [ 61 , 62 ], ethyl acetate [ 63 , 64 ], ethanol [ 65 ], acetone [ 66 , 67 ], chloroform [ 68 ], dimethyl sulfoxide [ 69 ], and methanol [ 70 ]. Due to its low water solubility, it is eliminated from the body at a fast rate, and therefore, its oral bioavailability is quite low.…”
Section: Curcuminmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it has exceptionally low water solubility (11 ng/mL in aqueous buffer pH 5.0), which means that it is eliminated from the body quickly and has a low oral bioavailability. It is soluble in dichloromethane [ 61 , 62 ], ethyl acetate [ 63 , 64 ], ethanol [ 65 ], acetone [ 66 , 67 ], chloroform [ 68 ], dimethyl sulfoxide [ 69 ], and methanol [ 70 ]. Due to its low water solubility, it is eliminated from the body at a fast rate, and therefore, its oral bioavailability is quite low.…”
Section: Curcuminmentioning
confidence: 99%
“…ii . β-amyloid content: thioflavin T (Tht) staining [ 61 , 76 , 77 , 78 , 79 ] silver staining [ 39 , 80 ], cresyl violet [ 81 ], alkaline phosphates [ 82 , 83 ], congo red [ 78 , 79 ], and ELISA assay [ 2 , 18 , 84 ]. iii .…”
Section: Figurementioning
confidence: 99%
“…It was observed that this combination improved the long-term memories and also inhibited the level of Aβ plaques circulated [ 163 ]. The investigations showed that the combination of micelles with Tween-80 to obtain curcumin micelles increases the efficacy and availability of curcumin to treat AD symptoms [ 164 ]. In the recent studies, the impact of PEG ceramide nanomicelles was analyzed on neuronal N2 cells which showed the high efficacy of nanomicelles in mediating tau proteins’ degradation and inducing autophagy in targeted cells.…”
Section: Evolution Of Treatment Strategiesmentioning
confidence: 99%
“…Moreover, it has been noted that curcumin-loaded nanomicelles suppressed the AD progression reducing protein fibrillation and inhibiting the amyloidogenesis through glycation process due to curcumin release, thus preventing the formation and accumulation of amyloid fibrils and glycation. This effect is also sustained by higher effectiveness of curcumin-loaded micelles due to their degradation or hydrolysis and subsequently the release of curcumin as an antioxidant agent [ 115 ].…”
Section: New Nanodelivery Strategies To Increase Pharmacological Activities Of Curcuminmentioning
confidence: 99%